Genetic loss of HIF-prolyl-hydroxylase 1, but not pharmacological inhibition, mitigates hepatic fibrosis - Tuffs, Christopher; Dupovac, Mareen; Richter, Katrin; Holten, Sophia; Schaschinger, Thomas; Marg, Oliver; Poljo, Adisa; Tasdemir, Ayse nur; Harnoß, Jonathan M.; Billeter, Adrian; Schneider, Martin; Strowitzki, Moritz (The American journal of pathology, 2025)
Liver fibrosis is characterized by excessive deposition of extracellular matrix due to chronic inflammation of the liver. Hepatic stellate cells (HSCs) become activated and produce increased amounts of extracellular matrix. Loss of HIF-prolyl-hydroxylase 1 (PHD1) attenuates HSC activation and fibrotic tissue remodeling in a murine model of biliary liver fibrosis. Herein, the protective effect of PHD1 deficiency (PHD1−/−) in an additional (toxic) model of liver fibrosis was validated and the effect of dimethyloxalylglycine (DMOG), a pan-HIF-prolyl-hydroxylase inhibitor, on the development of liver fibrosis, was evaluated. Liver fibrosis was induced utilizing carbon tetrachloride in wild-type (WT) and PHD1−/− mice treated with either vehicle or DMOG. To assess fibrosis development, expression of profibrotic genes in the livers was analyzed by Sirius red staining. When compared with WT mice, PHD1−/− mice developed less-severe liver fibrosis. DMOG treatment did not prevent this liver fibrosis. PHD1−/− mice had fewer α-SMA+ cells and less macrophage infiltration compared with WT mice. Expression of profibrogenic and proinflammatory genes was reduced in livers from carbon tetrachloride-exposed PHD1−/− mice. In vitro analyses of PHD1-deficient human HSCs revealed attenuated mRNA levels of profibrotic genes, as well as impaired migration and invasion. Although PHD1 deficiency attenuated activation of HSCs, pharmacologic PHD inhibition did not ameliorate fibrosis development. These data indicate that selective PHD1 inhibitors could prove effective in preventing and treating liver fibrosis.